2023
DOI: 10.3389/fpsyt.2023.1126689
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles and obsessive-compulsive symptoms in college students: the mediating role of perfectionism

Po Hu,
Pengwei Liang,
Xiaoyan Liu
et al.

Abstract: IntroductionObsessive-compulsive symptoms is a common psychological phenomenon among early adulthood college students, which are closely related to their parents’ parenting styles. Theoretical and some empirical studies have suggested the mediating role of perfectionism in this process, but this has not been confirmed, and the binary perspective of positive-negative perfectionism has not been addressed in this issue.MethodsThis study aimed to investigate the mediating role of perfectionism in the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This implies that degree rather than kind is the primary distinction between those with OCD and the general population. Therefore, normal people could also suffer from certain compulsive symptoms (Hu, Liang, Liu, et al, 2023).…”
Section: Theoretical Framework: Parenting Styles and Ocdmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that degree rather than kind is the primary distinction between those with OCD and the general population. Therefore, normal people could also suffer from certain compulsive symptoms (Hu, Liang, Liu, et al, 2023).…”
Section: Theoretical Framework: Parenting Styles and Ocdmentioning
confidence: 99%
“…Because obsessive-compulsive symptoms typically appear in the early stages of adulthood, researchers have concentrated on parenting styles, one of the most significant external influences linked to an individual's development during adolescence (Hu, Liang, Liu, et al, 2023). There are diverse studies on the relationship between parenting style and OCD in many countries around the world.…”
Section: Theoretical Framework: Parenting Styles and Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Research has revealed a significant association between parenting styles and attachment styles and moral disengagement. 22 Negative perfectionism plays a mediating role between a negative parenting style and obsessive-compulsive symptoms in college students, 23 and an authoritative parenting style is closely related to higher levels of social–emotional adjustment in preschool children. 24 In fact, responsive parenting styles have been shown to positively impact and reduce adolescent bullying behaviors.…”
Section: Introductionmentioning
confidence: 99%